Pelatihan Pengelolaan Sampah Rumah Tangga di Desa Pematang Johar, Deli Serdang - Mujahiddin; Yurisna Tanjung; Sahran Saputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of the Community Partnership Program (PKM) was carried out in Pematang Johar Village. This village was chosen because the waste management activities still use the Kumpul-Angkut-Dispose system. In addition, it is still a community member who manages waste by completing receiving waste, This PKM is carried out by providing training on waste management to the people in Pematang Johar Village. The method in this PKM activity is carried out with two approaches namely; socialization, training and FGD. The results of the PKM implementation show that: community group consisting of PKK Group and BUMDes Management Group have understood the practice of household scale waste management using the 3-R Principle. In addition, community groups have understood and are able to practice organic waste management into compost through the composter method. Community groups also understand and are able to practice inorganic waste management into creative goods such as piggy banks.